Heavy Metal Concentration (Pb, Cu, Cd, Zn) In Water And Sediments In Serangan Waters, Bali - Indrawan, Gede Surya; Putra, I Nyoman Giri (Metamorfosa: Journal of Biological Sciences, 2021)
Heavy metal pollution can disturb aquatic ecosystems and indicator of water quality. This study aims to determine the concentration of heavy metals (Pb, Cu, Cd, Zn) in water and sediments. This study was conducted in the waters of Serangan, South Denpasar District, Bali in June-August 2019. The research with each location taking 8 points of water and sediment sampling and measuring the quality of its waters. Water samples taken at the surface of the water as much as 330 ml and sediment samples taken as much as 500 grams. The method used is wet ashing preparation and analyzed by means of AAS ( Atomic Absorbsion Spektrophotometri ). The results of the average analysis of heavy metal concentrations in water are Pb 0 mg / L, Cd 0.438 mg / L, Cu 0 mg./L, and Zn 0.284 mg / L. The results of the analysis are compared with the standard quality value of sea water that the heavy metals Cd and Zn have exceeded the threshold. While the average concentration of heavy metals in sediments are Pb 17.444 mg / kg, Cd 18.093 mg / kg, Cu 113.981 mg / kg, and Zn 53.505 mg / kg. The concentration of Cd and Cu heavy metals exceeds the limits set by the ANZECC / ARMCANZ quality guidelines and the Canadian Council of Ministers of the Environment.